Infant morbidity and mortality attributable to prenatal smoking in Chile - Jaime Cerda; Claudia Bambs; Claudio Vera (Pan American Health Organization, 2017)
ABSTRACT Objective To estimate annual infant morbidity and mortality attributable to prenatal smoking in Chile during 2008−2012. Methods Population-attributable fractions (PAFs) for several infant outcomes were calculated based on previous study estimates of prenatal smoking prevalence and odds ratios associated with exposure (prenatal smoking relative to non-prenatal smoking). Prenatal smoking–attributable infant morbidity and mortality cases were calculated by multiplying the average annual number of morbidity and mortality cases registered in Chile during 2008–2012 by the corresponding PAF. Results PAFs for 1) births ≤ 27 weeks; 2) births at 28–33 weeks; 3) births at 34–36 weeks; and 4) full-term low-birth-weight infants were 12.3%, 10.6%, 5.5%, and 27.4% respectively. PAFs for deaths caused by preterm-related causes and deaths caused by sudden infant death syndrome were 11.9% and 40.0% respectively. Annually, 2 054 cases of preterm-birth and full-term low-birth-weight (1 in 9 cases), 68 deaths caused by preterm-related causes (1 in 8 cases), and 26 deaths caused by sudden infant death syndrome (1 in 3 cases) were attributable to prenatal smoking. Conclusions In Chile, infant morbidity and mortality attributable to prenatal smoking are unacceptably high. Comprehensive individual and population-based interventions for tobacco control should be a public health priority in the country, particularly among female adolescents and young women who will be the mothers of future generations.